1993
DOI: 10.1152/ajpgi.1993.264.5.g824
|View full text |Cite
|
Sign up to set email alerts
|

Effect of varying the rate and pattern of gastric distension on its sensory perception and motor activity

Abstract: The aim of the present study was to see if varying the rate and pattern of gastric distension affected its motor and sensory responses to distension. A balloon was used to carry out distensions in male volunteers at constant rates of 20, 50, 100, and 200 ml/min. In addition rapid (75 ml/s) intermittent distensions (RID) were carried out with the use of a large hand-held syringe. Subjects were asked to indicate the first perception of the balloon, fullness, and discomfort. Increasing the rate of ramp distension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…It can be stimulated by sight or activation of receptors in the stomach. By using a barostat, a bag which controls intraluminar pressure in a segment of the gut, it has been found that nausea can be induced by distension of the stomach (Khan, Read & Grundy, 1993). It is difficult to establish good animal models for symptoms like discomfort, bloating or postprandial fullness, and in studies on human subjects it is disappointing that the correlation between dyspeptic symptoms and findings on gastric barostat tests is low (Rhee et al , 2000).…”
Section: Interaction Of Biological and Psychological Factorsmentioning
confidence: 99%
“…It can be stimulated by sight or activation of receptors in the stomach. By using a barostat, a bag which controls intraluminar pressure in a segment of the gut, it has been found that nausea can be induced by distension of the stomach (Khan, Read & Grundy, 1993). It is difficult to establish good animal models for symptoms like discomfort, bloating or postprandial fullness, and in studies on human subjects it is disappointing that the correlation between dyspeptic symptoms and findings on gastric barostat tests is low (Rhee et al , 2000).…”
Section: Interaction Of Biological and Psychological Factorsmentioning
confidence: 99%
“…It is becoming increasingly apparent that afferent input from the gastrointestinal tract plays a very important role in the regulation of stomach and intestinal function (Melone and Mei, 1991;Raybould et al, 1991;Lloyd et al, 1992Lloyd et al, , 1993Brikas et al, 1993;Holzer, 1993;Khan et al, 1993;Chu et al, 1993). The principal recipient of this primary afferent information is the nucleus of the solitary tract (NST; Shapiro and Miselis, 1985;Altschuler et al, 1989Altschuler et al, , 1991.…”
mentioning
confidence: 99%
“…It is likely that intragastric sensory receptors exist in series with increasing stimulus intensity resulting in the recruitment of greater numbers of fibres, possibly changing a sensory stimulus from the stomach from perception to discomfort [21]. However, others have suggested that the sensory receptors lie in parallel with recruitment of either slow or rapidly adapting receptors determining the type of response [23]. This latter suggestion is supported by animal studies in which there appear to be high threshold vagal afferents [24].…”
Section: Discussionmentioning
confidence: 99%
“…Gastric sensitivity is related to the tone of the stomach wall, a reduced gastric tone being associated with a lower threshold for perception of distension [25]. The speed of balloon inflation affects sensory perception [21, 23]with slower distension rates resulting in a lower threshold of gastric perception and pain. The gastric muscle is viscoelastic, having reduced resistance to stretch with time, so that slow distension results in increased gastric compliance (greater intragastric volumes attained for each intragastric pressure increase).…”
Section: Discussionmentioning
confidence: 99%